Effect of Ferric Nitrate on Semi-Insulating 4H-SiC (0001) Chemical Mechanical Polishing. (1st November 2022) - Wang, Weilei; Liu, Weili; Song, Zhitang; Xu, Yonghui
Abstract : Semi-insulating 4H-SiC (0001) has high hardness and high chemical inertness, making it difficult to obtain high material removal rates (MRR) during chemical mechanical polishing (CMP). In this paper, the role of chemical additive ferric nitrate in semi-insulating 4H-SiC(0001) chemical mechanical polishing with α -alumina as abrasive and KMnO4 as oxidant was discussed. The results showed that 0.5 wt% ferric nitrate can increase the removal rate of semi-insulating 4H-SiC(0001) by 34%, while the semi-insulating 4H-SiC(0001) surface roughness Ra was reduced from 0.123 nm to 0.110 nm. The key point was that the coefficient of friction of the polishing slurry was effectively reduced, which was very beneficial to the ploughing effect of the α -alumina abrasive with vermicular thin section morphology which had the highest removal rate. In the second place, the chemical composition of 4H-SiC(0001) corrosion layer was analyzed by XPS under different corrosion conditions. Si 2P spectrum analysis showed that O atoms only attack C atoms to produce Si–C–O structure under acidic conditions. Whereas with the addition of ferric nitrate, O atoms not only attacked C atoms, but also attacked Si atoms to produce softer SiO2 and Si-Ox -Cy structures. At the end of the paper, the chemical mechanical polishing mechanism of semi-insulating 4H-SiC(0001) was given.